Social instability is associated with an elevated stress response but not with a fitness cost across vertebrate studies - Adriana A. Maldonado-Chaparro; Liam R. Dougherty; Loren D. Hayes; Luis A. Ebensperger (Royal Society Open Science, 2025)
Studies on single species often support that social instability influences physiological stress responses and individual fitness within social groups, yet the underlying mechanisms and adaptive consequences remain unclear. We conducted a meta-analysis spanning from 1970 to 2025, incorporating data from 59 articles across avian and mammalian species, to investigate the effects of social instability on stress and fitness. We found a positive association between social instability and glucocorticoid levels, consistent with our expectation of physiological response. Fitness declined with increasing social instability, but this relationship was not statistically significant and did not support our expectations. We found no statistically significant moderating effects of social system component, sex, age, taxonomic group and study type (experimental versus observational) on either stress or fitness outcomes. However, females and adults exhibited stronger positive stress correlations and stronger negative fitness correlations, and observational studies showed a similar trend when compared with experimental studies. Our results highlight a significant gap in the literature and call for greater taxonomic diversity and increasing use of experimental field studies to better understand the effects of social instability. Our meta-analysis further stresses the need for improved study standardization, as less than 20% of the publications examined were suitable for analysis.